Penggunaan Video ”Kenali Dan Cegah Stunting” Sebagai Media Edukasi Kesehatan Untuk Meningkatkan Pengetahuan Ibu Tentang Pencegahan Stunting Pada Balita: Bahasa Indonesia - Yuliati, Nunung; Yudianti, Ika; Yuliani, Ita (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2023)
Health behavior is influenced by knowledge, and knowledge can be improved through health education. Health education using audiovisual media has proven to be more effective than non-audiovisual. This study aims to determine the level of knowledge of mothers about stunting prevention in toddlers, who are given education using video media. Quantitative research design with quasi-experimental method with posttest only group approach. The samples in this study were mothers who had toddlers at Posyandu Anggrek, Dilem Village, Kepanjen District, Malang Regency in July 2022, which were taken using purposive sampling techniques and divided into experimental and control groups. The instrument used to measure the level of knowledge was questionnaire. After treatment with the stunting prevention video from the Indonesian Ministry of Health, the level of knowledge in the control group was in the good (22.2%), fair (27.8%), and less (50%) categories; while the treatment group using the stunting prevention video developed by researchers was in the good (27.8%), fair (38.5%), and less (33.3%) categories. The results of the Mann-Whitney test obtained ? value was 0.749 (?>0.05) which means there was no significant difference between the level of knowledge of respondents in the control group and the treatment group